A Russian paints America : the travels of Pavel P. Svinʹin, 1811-1813 - Svinʹin, Pavel P. (McGill-Queen's University Press, 2008)
The beginnings of Russian-American diplomatic relations / William Benton Whisenhunt -- A biography of Pavel Petrovich Svinʹin, 1787-1839 / William Benton Whisenhunt -- Travel in North America and the genre of the picturesque journey / Marina Swoboda -- A picturesque voyage through North America / Pavel P. Svinʹin ; translated by Marina Swoboda -- Appendix. Observations of a Russian in America : a look at the free visual arts in the United States of America / Pavel P. Svinʹin ; translated by Marina Swoboda -- Additional watercolours of North America / by Pavel P. Svinʹin.